Clinical presentation of pancreatic disorders: a prospective cohort study of 25 cases - Pahuja, Vivek; Singh, Sarabjit; Walia, Bhupinder S.; Dugg, Pankaj; Jain, Nitish (International Surgery Journal, 2024)
Background: Pancreatic disorders are one of the commonest abdominal disorders presented to a surgeon. The study focuses on demographic profile, clinical presentation and outcome of pancreatic disorders. Methods: All cases of pancreatic disorders admitted to surgical ward were included in this study. The clinical presentations, laboratory and radiographic investigations were recorded. Statistical analysis was done on SPSS software version 21. Results: Majority of patients belong to age group of 41-50 years (48%) with male predominance (3.2:1). However, the mean age was 36.06 years. Most common presentation was acute pancreatitis (68%) but the findings were not significant (p>0.05). Alcohol and biliary colic remained the majority of cause for pancreatic disorders. Conclusions: Pancreatic disorders are common in males in 5th decade of life. Alcohol and biliary calculi are the most common culprits for pancreatic disorders.